Analisis Dampak Penggunaan Media Sosial Terhadap Kesehatan Mental Dan Hubungan Sosial Mahasiswa Gen Z Unimed - Natalia Dela Br Simamora; Sani Susanti; Christiana Junita Panjaitan; Febry Yanti Br Ginting; Mas Iren Niat Anjelina Zebua (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This study aims to analyze the impact of social media use on the mental health and social relationships of Generation Z students at Universitas Negeri Medan. The frequent use of social media among this demographic is assumed to influence their psychological wellbeing, interaction patterns, and academic productivity. This research employed a descriptive qualitative approach through in-depth interviews, observation, and documentation involving three active university students as informants. The findings reveal that the students spend a significant amount of time accessing social media daily, predominantly using applications such as Instagram, TikTok, YouTube, and WhatsApp. Social media provides various benefits, including ease of communication, access to information, entertainment, and educational content that supports learning activities. However, uncontrolled use results in negative consequences, such as increased stress, anxiety, insecurity, difficulties in maintaining focus, and a tendency to procrastinate academic tasks. Moreover, face-to-face social interactions decline because students are more inclined to engage with digital platforms even when physically present with others. The study concludes that social media plays an essential role in students’ daily lives, yet its excessive use can disrupt mental well-being and interpersonal connections. Therefore, it is recommended that students regulate their digital habits, limit screen time, and enhance digital literacy to ensure that social media use remains balanced, healthy, and academically supportive. Keywords: social media, mental health, social relationships, Generation Z students, digital use, academic productivity. Abstrak Penelitian ini bertujuan untuk menganalisis dampak penggunaan media sosial terhadap kesehatan mental dan hubungan sosial mahasiswa Generasi Z di Universitas Negeri Medan. Penggunaan media sosial yang intens pada kelompok usia ini diperkirakan mempengaruhi aspek psikologis, interaksi sosial, dan produktivitas akademik mereka. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik wawancara mendalam, observasi, dan dokumentasi terhadap tiga mahasiswa aktif sebagai informan. Hasil penelitian menunjukkan bahwa mahasiswa menggunakan media sosial dalam durasi tinggi setiap hari, dengan aplikasi yang paling sering diakses adalah Instagram, TikTok, YouTube, dan WhatsApp. Media sosial memberikan manfaat berupa kemudahan mendapatkan informasi, hiburan, serta akses terhadap konten edukatif yang membantu proses pembelajaran. Namun, penggunaan yang tidak terkontrol menimbulkan dampak negatif berupa stres, kecemasan, perasaan tidak aman, gangguan konsentrasi, serta kecenderungan menunda tugas akademik. Selain itu, hubungan sosial tatap muka menurun karena perhatian mahasiswa lebih sering teralihkan pada perangkat digital saat berinteraksi langsung dengan orang lain. Penelitian ini menyimpulkan bahwa media sosial memiliki peran penting dalam kehidupan mahasiswa, tetapi penggunaannya perlu diatur secara bijak. Disarankan agar mahasiswa membatasi waktu penggunaan dan meningkatkan literasi digital agar mampu memanfaatkan media sosial secara sehat, seimbang, dan produktif. Kata Kunci: media sosial, kesehatan mental, hubungan sosial, mahasiswa Generasi Z, penggunaan digital, produktivitas akademik.